Healthcare practitioners’ views of social media as an educational resource - Pizzuti, Adam G. (PLoS One, 2020)
Social media is increasingly utilized as a resource in healthcare. We sought to identify perceptions of using social media as an educational tool among healthcare practitioners. An electronic survey was distributed to healthcare administrators, nurses, nurse practitioners, pharmacists, physicians, and physician assistants f hospital systems and affiliated health science schools in Georgia, Maryland, South Carolina, and Wisconsin. Survey questions evaluated respondents’ use and views of social media for educational purposes and workplace accessibility using a Likert scale (1 = strongly disagree, 5 = strongly agree). Nurses (75%), pharmacists (11%), and administrators (7%) were the most frequent respondents. Facebook® (27%), Pinterest® (17%), and Instagram® (17%) were the most frequently accessed social media platforms. Nearly 85% agreed or strongly agreed that social media can be an effective tool for educational purposes. Among those who had social media platforms, 43.0% use them for educational purposes. Pinterest® (30%), Facebook® (22%), LinkedIn® (16%), and Twitter® (14%) were most frequently used for education. About 50% of respondents had limited or no access to social media at work. Administrators, those with unlimited and limited work access, and respondents aged 20–29 and 30–39 years were more likely to agree that social media is an educational tool (OR: 3.41 (95% CI 1.31 to 8.84), 4.18 (95% CI 2.30 to 7.60), 1.66 (95% CI 1.22 to 2.25), 4.40 (95% CI 2.80 to 6.92), 2.14 (95% CI 1.53 to 3.01) respectively). Residents, physicians, and those with unlimited access were less likely to agree with allowing social media access at work for educational purposes only. Healthcare practitioners frequently utilize social media, and many believe it can be an effective educational tool in healthcare.